2007
DOI: 10.1111/j.1447-0756.2007.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laparoscopic cystectomy on fecundity of infertility patients with ovarian endometrioma

Abstract: Laparoscopic surgery should be performed prior to ART treatment not only for making a decision about the treatment course but also for establishing a good pelvic condition to induce a pregnancy during ART treatment in infertility treatment with ovarian endometrioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Nakagawa et al [4] expressed major concern about the loss of follicles associated with the stripping procedure. But in both the randomized control studies of Beretta et al [6], Alborzi et al [7] and Hye et al [8] the spontaneous pregnancy was significantly greater in the excision group 66.7% vs 23.5%, 59.3%vs 23.3% and 38.9% vs 11.1% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakagawa et al [4] expressed major concern about the loss of follicles associated with the stripping procedure. But in both the randomized control studies of Beretta et al [6], Alborzi et al [7] and Hye et al [8] the spontaneous pregnancy was significantly greater in the excision group 66.7% vs 23.5%, 59.3%vs 23.3% and 38.9% vs 11.1% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Nakagawa et al [4] state that the presence of endometriosis is thought to reduce fecundity, therefore cystectomy is commonly performed for endometriomas more than 3 cm in diameter before ART treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since an ovarian endometrioma itself reduces fecundity in infertile patients, the removal of it might be an optimal treatment. Indeed, our recent report indicated that laparoscopic removal of an ovarian endometrioma had significant benefits for infertile patients, including an improved pregnancy outcome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently we reported that removal of endometriomas improved fecundity [19], and another report showed that, despite a reduction in ovarian reserve following laparoscopic cystectomy, pregnancy rate was unaffected [20]. In women who underwent unilateral cystectomy, the mean number of oocytes retrieved from the operated ovary was significantly less than that obtained from the contralateral, non-operated-ovary [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a consensus that operative laparoscopy should be considered the first line treatment in symptomatic women with endometriomas [3,4], there is ongoing debate on how to manage endometriomas before attempting assisted reproductive technology (ART) treatment. Some investigators have indicated that ovarian surgery might improve the fecundity of infertility patients with ovarian endometriomas [5,6]. However, others have not reported improvements in pregnancy rate following surgical treatment in the context of ART [7].…”
Section: Introductionmentioning
confidence: 99%